Pengaruh Variasi Waktu Perendaman dalam Ekstrak Daun Teh Hijau (Camellia sinensis) terhadap Stabilitas Dimensi Alginat - Prabowo, Yoghi B.; Ibrahim, Natalia P.; Saraswati, Indah (e-GiGi, 2021)
Abstract: Alginate has an imbibition property if it comes in contact with water that will affect the dimensional stability. Green tea (Camellia sinensis) contains phenolic compounds which can minimize the imbibition process while it is used in disinfection of alginate impression. This study was aimed to analyze the differences in the dimensional stability of alginate impressions after immersion in green tea leaf extract based on time variation. This was an experimental post-test laboratory study only. The one way Anova test on the anteroposterior and mediolateral dimensions showed that variation of immersion time in 50% green tea leaf extract could affect the dimensional stability. Moreover, the post hoc Games Howell test on the anteroposterior dimension and the post hoc LSD test on the mediolateral dimension resulted that there were significant differences between the control group and the groups of 5 minutes, 15 minutes, 30 minutes, and 50 minutes of immersion. Among all alginate impressions, the one immersed for 15 minutes was still in accordance with the standard of the American Dental Association. In conclusion, 15-minute immersion of alginate impression in 50% green tea leaf extract was the best time variation.Keywords: alginate, dimensional stability, green tea leaf extract 50% Abstrak: Alginat memiliki sifat imbibisi bila berkontak dengan air yang akan memengaruhi stabilitas dimensi alginat. Teh hijau (Camellia sinensis) mengandung senyawa fenol yang mampu meminimalkan terjadinya proses imbibisi. Penelitian ini bertujuan untuk menganalisis perbedaan stabilitas dimensi alginat setelah direndam berdasarkan variasi waktu dalam ekstrak daun teh hijau. Jenis penelitian ialah eksperimental laboratorik post-test only. Stabilitas dimensi diketahui melalui selisih jarak anteroposterior (A’-B’) dan mediolateral (B’-C’) master die dengan die stone. Hasil uji one way Anova terhadap dimensi anteroposterior dan mediolateral mendapatkan adanya pengaruh variasi waktu perendaman dalam ekstrak daun teh hijau 50% terhadap stabilitas dimensi. Selanjutnya hasil uji post hoc Games Howell terhadap dimensi anteroposterior dan uji post hoc LSD terhadap dimensi mediolateral mendapatkan perbedaan bermakna antara kelompok kontrol dengan kelompok perendaman 5 menit, 15 menit, 30 menit, dan 50 menit. Hasil perendaman cetakan alginat yang masih sesuai dengan standar American Dental Association ialah perendaman selama 15 menit. Simpulan penelitian ini ialah perendaman cetakan alginat dalam ekstrak daun teh hijau 50% yang terbaik ialah selama 15 menit.Kata kunci: alginat, stabilitas dimensi, ekstrak daun teh hijau 50%